2017
DOI: 10.1038/s41598-017-16738-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for OATP2A1/SLCO2A1 in a murine model of colon cancer

Abstract: Prostaglandin E2 (PGE2) is associated with proliferation and angiogenesis in colorectal tumours. The role of prostaglandin transporter OATP2A1/SLCO2A1 in colon cancer tumorogenesis is unknown. We evaluated mice of various Slco2a1 genotypes in a murine model of colon cancer, the adenomatous polyposis (APC) mutant (Apc ∆716/+) model. Median lifespan was significantly extended from 19 weeks in Slco2a1 +/+/Apc Δ716/+ mice to 25 weeks in Slco2a1 −/−/Apc Δ716/+ mice. Survival was directly related to a reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…We found that SLCO2A1 is essential for the PTGS reaction. Blocking SLCO2A1 has been shown to reduce colon cancer tumorigenesis 53 . Importantly, SLCO2A1 can be potently and selectively inhibited by the FDA approved drug suramin 54 .…”
Section: Resultsmentioning
confidence: 99%
“…We found that SLCO2A1 is essential for the PTGS reaction. Blocking SLCO2A1 has been shown to reduce colon cancer tumorigenesis 53 . Importantly, SLCO2A1 can be potently and selectively inhibited by the FDA approved drug suramin 54 .…”
Section: Resultsmentioning
confidence: 99%
“…The authors presume that this homeostasis is impaired in gastric tumors due to the negative regulation of SLCO2A1 and, consequently, the negative regulation of PGE 2 degradation, resulting in the enhancement of PGE 2 signaling and gastric tumorigenesis [ 53 ]. Contrary to those reports, a study by Nakanishi et al [ 54 ] suggests an association between higher SLCO2A1 expression in colorectal cancer and poor prognosis. The authors indicate a likely promotion of tumorigenesis by PGE 2 uptake into the endothelial cells via this transporter [ 54 ].…”
Section: Discussionmentioning
confidence: 70%
“…In fact, intestinal epithelial-specific Slco2a1-deficient mice has lower susceptibility to experimental colitis as with the model in the study by Zhang et al Although suppressed PGE 2 metabolism in macrophages might contribute to the enhanced PGE 2 concentration, Slco2a1 ΔMP only partially reproduced the systemic knockout phenotype in the present study. As SLCO2A1 is mainly expressed on vascular endothelial cells in the intestinal tracts of mice 47 and humans 12 , a decrease in the clearance of PGE 2 from vascular endothelial cells might also contribute to the increase in the PGE 2 concentration around macrophages in the intestine. Further studies will clarify the role of SLCO2A1 on endothelial cells in intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%